Gelatin and non gelatin soft gel capsules: A review - Chavarría Rojas, Marianela (2021)
Soft gelatin capsules are solid, single-dose dosage forms consisting of a shell, usually made from gelatin, that generally contain liquids. Gelatin is the most widely used film-forming agent, and it is extracted from collagen through hydrolysis. However, it is also possible to use starch and cellulose derivatives, such as hydroxypropyl methylcellulose, to form the thin ribbons required for the production of soft gel capsules. The most widely used method for making and filling soft gel capsules is using a rotary die process which is known as the first continuous manufacturing process. Due to the nature of soft gelatin capsules, the to-be-encapsulated liquid formulation must be within well-established moisture and pH limits. These liquids can be either hydrophilic or hydrophobic and can be formulated as solutions or suspensions. There are currently many soft capsules patents, some covering formulations and others covering the processes of soft capsules without incorporating gelatin. The main objective of this paper was to review both soft gelatin and non-gelatin capsules as to their general aspects, composition, manufacturing processes, and controls affecting this pharmaceutical dosage form. Additionally, some patents for soft gelatin and non-gelatin capsules are cited.